Lipidomics insight into chronic exposure to ambient air pollution in mice. (July 2020) - Li, Ran; Wang, Yixuan; Hou, Biyu; Lam, Sin Man; Zhang, Wenhui; Chen, Rucheng; Shui, Guanghou; Sun, Qinghua; Qiang, Guifeng; Liu, Cuiqing
Abstract: More recent evidences are supportive of air pollution exposure on diabetes risk, including worsening of whole-body insulin sensitivity, enhancement of hepatic lipogenesis and nonalcoholic fatty liver disease after fine particulate matter (PM2.5 ) exposure. Therefore, we aimed to explore the lipidomics to get a comprehensive insight about ambient real-world PM2.5 exposure on lipid metabolism in blood and liver. After ambient PM2.5 exposure for 6 months, excess triglyceride accumulation in the liver was observed. Remarkable metabolic alterations including neutral lipids, glycerophospholipids and sphingolipids were noticed. Lipidomic signatures in liver is different from plasma in response to PM2.5 exposure. Lipids including species of ceramide, sphingomyeline and triglyceride may become potential biomarkers of lipotoxicity contributing to PM2.5 -induced metabolic dysfunction, and the present study may serve as a reference lipid bank for further studies. Graphical abstract: Image 1 Highlights: Excess triglyceride accumulation in the liver was induced by ambient PM2.5 exposure.Lipidomic signatures in the liver were different from that in plasma. Lipidomic signatures in the liver were different from that in plasma. Potential biomarkers of lipotoxicity were identified for the adverse effects. Abstract : Capsule summarize: Ceramide, sphingomyeline and triglyceride are potential biomarkers for the adverse metabolic health after PM2.5 exposure.